Regular algorithms for the analysis of radio-location images - Ageev, A.L.; Korshunov, M.E. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2007)
The problem of navigation on the basis of radio-location images is considered. The image distortions are described by a convolution-type Fredholm integral equation of the first kind and by a statistical noise. In order to solve the navigation problem, it is necessary to determine, with a high accuracy, the coordinates of the point from which an image is formed. To accomplish this, a comparison is performed between this image and the master image obtained with the use of an area map. A new regularization algorithm is proposed to enhance the accuracy of determining the coordinates. Some results of model computations are discussed.